Single Parent Hood and Family Welfare: A Case Study of Murora Sub- County Kisoro District. - Nyiramugisha, Happy (Kabale University, 2023)
Single parenthood faces multiple challenges in attempts to manage family services like clothing. However, access to services presents insurmountable obstacles to single parents. Single parenting parents, work full-time alone to provide for dependents' basic needs while maintaining benefits to ensure that their families still survive. The researcher investigated single parenthood and family welfare in Murora sub-county Kisoro district.